Distribution and luminescence characteristics of Ce³⁺ ions in calcium hydroxyapatite - Berezovskaya, I.V.; Efryushina, N.P.; Stryganyuk, G.B.; Voloshinovskii, A.S.; Zubar, E.V.; Dotsenko, V.P. (Functional Materials, 2008)
The luminescence characteristics of Ce³⁺ ions in calcium hydroxyapatite Ca₁₀(PO₄)₆(OH)₂ have been studied under excitation within the 3.5-15 eV region. It has been found that in Ca₁₀(PO₄)₆(OH)₂ prepared in a reducing atmosphere, Ce³⁺ ions tend to occupy preferably high symmetry Ca(I) sites. The energies of all 5d crystal field levels of Ce³⁺ ions in Ca(I) sites have been determined. In addition to the 4f->5d excitation bands, the excitation spectrum of the Ce³⁺ emission shows a band with a maximum at 7.7 eV which is attributed to the host lattice absorption. The influence of the structural features of Ca₁₀(PO₄)₆(OH)₂ on the luminescent behavior of Ce³⁺ is discussed. Вивчено люмінесцентні властивості іонів Ce³⁺ у гідроксіапатиті кальцію Ca₁₀(PO₄)₆(OH)₂ при збудженні в області 3,5-15 еВ. Встановлено, що у Ca₁₀(PO₄)₆(OH)₂, одержаному у відновлювальному середовищі, іони Ce³⁺ виявляють тенденцію займати високосиметричні Са(І)-позиції. Визначено енергії всіх компонентів 5d-конфігурації іонів Ce³⁺ у позиціях Са(І). у спектрі збудження люмінесценції іонів Ce³⁺, крім 4f->5d смуг, також спостерігається смуга з максимумом 7,7 еВ, що обумовлена власним по- глинанням гідроксіапатиту кальцію. Обговорюється вплив структурних особливостей Ca₁₀(PO₄)₆(OH)₂ на люмінесцентні властивості іонів Ce³⁺. Изучены люминесцентные свойства ионов Ce³⁺ в гидроксиапатите кальция Ca₁₀(PO₄)₆(OH)₂ при возбуждении в области 3,5-15 эВ. Установлено, что в Ca₁₀(PO₄)₆(OH)₂, полученном в восстановительной среде, ионы Ce³⁺ проявляют тенденцию занимать высокосимметричные Са(l) позиции. Определены энергии всех компонентов 5d-конфигурации ионов Ce³⁺ в позициях Са(l). В спектре возбуждения люминесценции ионов Ce³⁺, помимо полос 4f->5d, также наблюдается полоса с максимумом 7,7 эВ, которая обусловлена собственным поглощением гидроксиапатита кальция. Обсуждается влияние структурных особенностей Ca₁₀(PO₄)₆(OH)₂ на люминесцентные свойства ионов Ce³⁺.